Exercise-Based Cardiac Rehabilitation Improves Cognitive Function Among Patients With Cardiovascular Disease. Issue 6 (November 2020) - Moriarty, Terence A.; Bourbeau, Kelsey; Mermier, Christine; Kravitz, Len; Gibson, Ann; Beltz, Nicholas; Negrete, Omar; Zuhl, Micah
Abstract : Purpose: To investigate the effects of cardiac rehabilitation (CR) exercise training on cognitive performance and whether the changes are associated with alterations in prefrontal cortex (PFC) oxygenation among patients with cardiovascular disease. Methods: Twenty (men: n = 15; women: n = 5) participants from an outpatient CR program were enrolled in the study. Each participant completed a cognitive performance test battery and a submaximal graded treadmill evaluation on separate occasions prior to and again upon completion of 18 individualized CR sessions. A functional near-infrared spectroscopy (fNIRS) device was used to measure left and right prefrontal cortex (LPFC and RPFC) oxygenation parameters (oxyhemoglobin [O2 Hb], deoxyhemoglobin [HHb], total hemoglobin [tHb], and oxyhemoglobin difference [Hbdiff]) during the cognitive test battery. Results: Patients showed improvements in cardiorespiratory fitness (+1.4 metabolic equivalents [METs]) and various cognitive constructs. A significant increase in PFC oxygenation, primarily in the LPFC region, occurred at post-CR testing. Negative associations between changes in cognition (executive function [LPFC O2 Hb: r = −0.45, P = .049; LPFC tHb: r = −0.49, P = .030] and fluid composite score [RPFC Hbdiff: r = −0.47, P = .038; LPFC Hbdiff: r = −0.45, P = .048]) and PFC changes were detected. The change in cardiorespiratory fitness was positively associated with the change in working memory score ( r = 0.55, P = .016). Conclusion: Cardiovascular disease patients enrolled in CR showed significant improvements in multiple cognitive domains along with increased cortical activation. The negative associations between cognitive functioning and PFC oxygenation suggest an improved neural efficiency. Abstract : Supplemental Digital Content is Available in the Text.Exercise-based cardiac rehabilitation (CR) increases prefrontal cortex oxygenation and improves cognitive performance. However, this does not appear to be responsible for the improvement in cognitive performance. One such adaptation to the CR exercise intervention may be an improvement in neural efficiency. In conclusion, CR produces benefits beyond one's aerobic capacity.